COOPERATIVE LEARNING IN FLIPPED CLASSROOM ON INDONESIAN EFL STUDENTS' READING PROFICIENCY: AN EXPERIMENTAL STUDY - Aksendro Maximilian; Galuh Dwi Ajeng (Universitas Muhammadiyah Kotabumi, 2023)
Addressing the post-pandemic challenges in EFL classroom, teacher should empower their knowledge by exploring the potential methods to be applied in the classroom (Bawawa et al., 2021). Combining cooperative learning and flipped classroom can be a way for answering the challenges in post pandemic period. Some researchers have positively suggested about the integration of cooperative learning method in flipped classroom (Erbil, 2020; Linling & Abdullah, 2023). However, the studies about the combination of these methods are still limited (Aslan, 2022; Foldnes, 2016). Therefore, this research attempts to examine cooperative learning implication in flipped classroom effects for EFL students’ reading achievement during post-pandemic period. This study employs the quasi-experimental research. The experimental group is taught using the integration of cooperative learning into flipped classroom model, whereas, control group is taught using conventional instruction. The findings reveal that the students who learn in experimental group have better reading performance than those who learn in control group. The finding also presents that the integration of cooperative learning and flipped classroom have statistically significant effects towards reading proficiency. Thus, this study proposes an adaptive instructional model to enhance students’ English language communication and skills.